Assessment of farmers' adoption of kasechar technology for agricultural waste management in Chachoengsao Province, Thailand - Eain Dray Aung; Sasaki, Nophea; Tsusaka, Takuji W.; Chaklam Silpasuwanchai; ADB-Japan Scholarship Program (ADB-JSP) (Pathum Thani : Asian Institute of Technology, 2025)
Burning crop residues is common in many developing regions, including Thailand, and contributes to air pollution and environmental damage. Modern technologies like mobile applications can help improve productivity and support sustainable waste management by offering alternatives to traditional methods, reducing costs, and increasing market access. However, there is a lack of research on how small-scale farmers, especially Participatory Guarantee System (PGS) farmers in Thailand, adopt such technologies. This study aims to assess the adoption of KaseChar technology for agricultural waste management in Chachoengsao Province, Thailand, by evaluating farmers' perceptions of its usefulness (PU), ease of use (PEOU), and behavioral intention (BI), while analyzing the key factors influencing these aspects, along with other external determinants. The technology used in this research is KaseChar, which is a digital marketplace designed to improve local livelihoods and address the environmental issue of agricultural waste burning in rural areas. Using the Technology Acceptance Model (TAM), the study evaluates farmers' perceptions of KaseChar, focusing on perceived usefulness (PU), perceived ease of use (PEOU), and behavioral intention (BI) to adopt the technology. The research also examines external factors influencing these perceptions, such as cost concerns, market conditions, and social influence. A mixed-method approach was used, combining quantitative data from 150 farmers with qualitative insights from 11 respondents from focus group discussions (FGDs) and 5 key informant interviews (KIIs) involving farmer leaders and government officials. Statistical analyses, including descriptive statistics, exploratory factor analysis (EFA), and probit regression, were conducted with quantitative data, while content analysis was conducted with qualitative data. The study revealed that farmers demonstrated a positive attitude toward adopting the KaseChar app for agricultural waste management. Key factors such as perceived productivity, efficiency, proficiency, social influence, and waste management costs positively and significantly influenced farmers{u2019} willingness to adopt the technology. Farmers with higher internet usage and waste management expenses demonstrated stronger confidence in technical skills and app efficiency, while younger farmers exhibited greater interest in adoption. Despite favorable perceptions, barriers like limited digital literacy, high costs, and logistical challenges persist. Addressing these through simplified app interfaces, financial incentives, and expanded training programs can enhance adoption and promote sustainable agricultural waste management practices. However, barriers such as high labor and transportation costs, limited market access, and digital literacy among older farmers remain significant challenges. FGDs highlighted logistical concerns, such as the need for buyers to handle transportation, while KIIs emphasized the importance of government support and awareness campaigns. Key strategies for increasing technology adoption include enhancing extension services, offering financial incentives, integrating carbon credits, and improving digital infrastructure. These findings offer valuable insights for policymakers, developers, and stakeholders to promote sustainable agricultural practices. Future research should focus on government support for digital marketplaces to reduce agriwaste burning, improving waste transportation for trade, enhancing digital literacy, evaluating the fully developed KaseChar app{u2019}s impact, and conducting comparative studies with diverse samples to understand adoption behaviors.
A thesis submitted in patial fulfillment of the requirements for the degree of Master of Science in Natural Resources Management
Thesis (M. Sc.) - Asian Institute of Technology, 2025
Keywords: Agricultural wastes -- Thailand -- Management; Agricultural applications; Agricultural innovations